INTERNATIONAL METHODS OF A MODERN APPROACH TO PRESCHOOL EDUCATION - Karimova Shoira Bakhtiyarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article is devoted to the foundation of a new paradigm of preschool education, which is the factor that makes up the system to create a new paradigm of Education, based on the heuristic possibilities of the concept of functional asymmetry of the human brain.